2014
DOI: 10.5130/ijcre.v7i1.3389
|View full text |Cite
|
Sign up to set email alerts
|

University and community partnerships in South Sulawesi, Indonesia: Enhancing community capacity and promoting democratic governance

Abstract: South Sulawesi is a province in Indonesia where the majority of the population is Muslim, with many variant interpretations of Islam. Alauddin State Islamic University is not just a place for teaching and study but also plays a role in helping to unify the differences among these different Islamic groups. Its changing of status from institute to university in 2005, and later the support of the Canadian-assisted SILE Project beginning in 2010, have made this university an example of reform in the way it impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Such alliance is therefore a co-dependent relationship [11] that facilitates resource sharing and the pooling of diverse knowledge and skill sets, with a collective goal of addressing critical issues [12]. The higher educational system is mainly tasked with "teaching, research, and community service/engagement" [13] (p. 164). Porter [3] observed that the service/engagement component is the most obscure of the three functions, despite being a key element in educational planning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Such alliance is therefore a co-dependent relationship [11] that facilitates resource sharing and the pooling of diverse knowledge and skill sets, with a collective goal of addressing critical issues [12]. The higher educational system is mainly tasked with "teaching, research, and community service/engagement" [13] (p. 164). Porter [3] observed that the service/engagement component is the most obscure of the three functions, despite being a key element in educational planning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They play a key role in university curriculum development [4] and are therefore central in the effort to align Agricultural Education and Training (AET) curricula with the current issues facing South Africa's agricultural sector. Real situational experiences from such alliances can become a resource that influences teaching and learning [13]. Porter [3] noted some potential benefits for each engaging party: (a) it is a platform for community members to benefit from the technical assistance, time, energy, resources, and know-how of the university student and staff; (b) universities are able to deliver on their mandate to engage in community development; (c) students are able to get involved in applied learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This practice does not contribute much to empowering the community and thus, being a successful platform for a service-learning environment. In an Asian study, it was reported that universitycommunity engagement programme failed to fulfill many of the CSL principles including community empowerment (Mastuti et al, 2014).…”
mentioning
confidence: 99%
“…As a result, meaningful collaborative partnership and positive social change in promoting social equity among communities may be possible through CSL (Ochocka & Janzen, 2014). Approaching the local community, interacting with them, helping to increase their competency based on the community's strengths, readiness of each counterparts (university and community) to manage time and work both in program planning and implementation and to change the mindset of all the parties involved are some of the challenges highlighted in implementing CSL (Mastuti et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation